Comparison of active and physiologic management of third stage of labor - F Vasegh Rahimparvar; A Bahiraie; M Mahmoudi; L Salehi (Tehran University of Medical Sciences, 2005)
Introduction: The delivery of placenta and membranes (third stage of labor) is an important stage of delivery. Complications of this stage can increase maternal mortality rate. There is controversy regarding the routine use of oxytocic drugs in this stage of labor. These drugs may shorten duration of third stage but have side effects. Furthermore, management of delivery in physiologic way causes minimum damage to the mother and newborn. Materials and Methods: The present research is a clinical trial study. A total of 94 subjects were divided into two groups. All subjects in active group received 10 units of Syntocinon in 500 cc serum. The cord was clamped and cut after cessation of pulsation and the placenta was delivered by Brandt-Andrews maneuver. Women in the physiologic group received 1cc of placebo in 500 cc serum, no clamping of the cord was attempted until pulsation had ceased and the placenta was delivered by minimal traction on the cord and with maternal effort without any maneuver. Results: Two groups were matched in the subjects' characteristics. The rate of postpartum hemorrhage in physiologic group (14.58%) was higher than active group (10.64%) but the statistical tests showed no significant differences between two groups (p=0.2945). The mean duration of the third stage of labor in the physiologic group (13 minutes) was longer than active group (9 minutes) but the statistical test showed no significant differences between two groups. The statistical tests also showed no significant differences between rate of retained placenta (p=0.5) or piece of the placenta and membranes (0.2428) in two groups. Conclusion: Statistical tests showed no significant differences between duration and complications of the third stage of labor in two groups. The routine use of Syntocinon in management of third stage of labor can not be recommended.